Rapid and Facile Preparation of Giant Vesicles by the Droplet Transfer Method for Artificial Cell Construction - Shimane, Yasuhiro; Kuruma, Yutetsu (Frontiers in Bioengineering and Biotechnology, 2022)
Giant vesicles have been widely used for the bottom-up construction of artificial (or synthetic) cells and the physicochemical analysis of lipid membranes. Although methods for the formation of giant vesicles and the encapsulation of molecules within them have been established, a standardized protocol has not been shared among researchers including non-experts. Here we proposed a rapid and facile protocol that allows the formation of giant vesicles within 30 min. The quality of the giant vesicles encapsulating a cell-free protein expression system was comparable to that of the ones formed using a conventional method, in terms of the synthesis of both soluble and membrane proteins. We also performed protein synthesis in artificial cells using a lyophilized cell-free mixture and showed an equivalent level of protein synthesis. Our method could become a standard method for giant vesicle formation suited for artificial cell research.